STATISTIKA DESKRIPTIF T-TEST UNTUK MEMPERMUDAH PEMILIHAN DATA DARI HASIL PENGUJIAN BETON MENGGUNAKAN SPSS 16.0 - Nevy Risna Dyah Kumala; Ratih Pujiastuti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
This study discusses the application of descriptive statistics in the world of construction projects to analyze and interpret the data under study. Considering that time is a crucial thing in the project, it is necessary to have auxiliary tools to increase the time usage effectively for all important elements in the construction project. One of them is to shorten the time to analyze research results from testing concrete or concrete mixtures with case studies. To achieve maximum results, it takes a lot of samples that produce a lot of data. Hence, this study tries to use T-Test analysis of descriptive statistics which can help compare related groups to find out whether there are differences between groups. The results of the case study showed that there was no significant difference between concrete with normal mixture and other mixtures. Thus, the results of the study analysis can be concluded immediately whether the quality of the concrete according to the design criteriaKeywords: Descriptive Statistic, T-Test, The Quality of concrete